Loneliness and cognitive impairment among older people in long-term care - Syed Elias, Sharifah Munirah; Makhtar, Aniawanis; Azizan, Azzirat Farhana (2019)
Loneliness and cognitive impairment are common among older people. However, the study on the association between cognitive impairment and loneliness among older people in long-term care in Malaysia is limited. This study aimed to explore the association between socio-demographic, cognitive impairment and loneliness among older people in long-term care. A cross-sectional study was conducted on 167 older people aged 60 years and over living in long-term care (Rumah Seri Kenangan Ulu Kinta, Perak and Rumah Seri Kenangan Cheras, Selangor). A questionnaire consists of three parts; socio-demographic background, Elderly Cognitive Assessment Questionnaire (ECAQ) and University of California, Los Angeles (UCLA) Loneliness Scale were used for data collection. Data were analysed by using IBM Statistical Package Social Science (SPSS) version 20. It was found that 51.5% of older people experienced a severe high degree of loneliness. For the cognitive level, 49.1% older people reported having cognitive impairment. There was a significant association between age and loneliness (p = 0.001). It was reported that there was a significant association between age (p = 0.003), marital status (p = 0.006) and cognitive level. This study also found that there was a strong positive correlation between cognitive impairment and loneliness (r = 0.832, p = 0.001). The findings suggest a pressing need for interventions designed to decrease loneliness that may be particularly beneficial for the reduction of cognitive impairment among older people living in long-term care.